2017
DOI: 10.4028/www.scientific.net/msf.885.190
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of TIG Welded Joints of Stainless Steels

Abstract: The aim of this work was to analyze the performance of joints made by TIG (Tungsten Inert Gas) welding process in austenitic and duplex stainless steels with special regards to their corrosion resistance. Three different types of stainless steel were butt welded with TIG method. Ferric-chloride test and electrochemical treatments revealed how does the TIG process affects the corrosion resistance depending upon the alloy used for welding the joint. This work focuses on the weldability of the 2304, 2404 and 304 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…From Table 5, it can be clearly seen that although the arc energies were kept constant, the increasing N 2 content in the shielding gas means increasing amount of heat during TIG welding, which is represented in the increasing values of WM geometries. This observation was taken into account during the solution of the theoretical model in Equations (2), (21), (26), and (27).…”
Section: Weld Geometry Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Table 5, it can be clearly seen that although the arc energies were kept constant, the increasing N 2 content in the shielding gas means increasing amount of heat during TIG welding, which is represented in the increasing values of WM geometries. This observation was taken into account during the solution of the theoretical model in Equations (2), (21), (26), and (27).…”
Section: Weld Geometry Resultsmentioning
confidence: 99%
“…Thus, the base materials' (BMs) nitrogen content plays a significant role during DSS welding. During arc welding of DSSs, the nitrogen loss from the weld metal (WM) leads toward more ferritic microstructures and to the loss of the abovementioned properties [21,22]. In order to balance this nitrogen loss, nitrogen (N 2 )-argon (Ar) (or helium) mixed shielding gases are used in industrial applications for DSS tungsten inert gas (TIG) welding [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, to obtain a weld joint with two more balanced phases and higher mechanical properties, it is not enough to only regulate the welding heat input. Alcantara et al [ 12 ] used Ar as the shielding gas to weld 2304 duplex stainless steel by TIG and found that the loss of N in the molten pool was serious. The ferrite content in both the weld metal and HAZ was relatively high compared to BM.…”
Section: Introductionmentioning
confidence: 99%
“…The condition for corrosion resistance is a stable, contiguous, passive layer on the steel surface. This is met when Cr ≥ 12% and C ≤ 1.2% [3][4][5][6]. This resistance is provided by the chromium-oxide ( Cr 2 O 3 ) [7] on the surface of the steel if the amount of Cr is higher on the surface than inside of the material.…”
Section: Introductionmentioning
confidence: 99%